Research on Mode Shift Control of Multimode Hybrid Systems Based on Hybrid Model Prediction - Xinxin Zhao; Jiadian Liu; Bing Li (World Electric Vehicle Journal)
A hybrid mining dump truck contains multiple power sources and has a variety of operating modes. When the vehicle switches between different operating modes, inappropriate control strategies will result in insufficient power or excessive output torque ripple. The resulting vehicle shock and the dynamic characteristics of the dynamic clutch mechanism will affect ride comfort. In order to improve the performance of the hybrid mining dump truck in the mode switching process as much as possible, this paper takes power-split hybrid special transmission as the research object and proposes a hybrid model predictive control (HMPC) strategy. However, the simulation time of the HMPC algorithm is about 27% less than that of the MPC algorithm. HMPC can significantly shorten the control time while improving the vehicle ride comfort, reducing the sliding friction work during mode switching, and improving the real-time and robustness of mode switching.